Revisão sistemática do gênero phoenicircus (aves: cotingidae) com base em morfometria e caracteres de plumagem - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2008)
The genus Phoenicircus (Aves: Cotingidae) is composed of two exclusively Amazonian species with a largely parapatric distribution: P. carnifex (Linnaeus 1758) and P. nigricollis (Swainson 1832). Phoenicircus carnifex is known predominantly from the Guiana shield, reaching, however, the lower Madeira, Tapajós and Tocantins rivers in eastern Amazonia, including the Belém region (TRAYLOR,1979; RIDGELY; TUDOR, 1994). On the other hand, P. nigricollis is distributed mainly in Western Amazonia, from the west bank of the Negro River to the east bank of the Tapajós River (TRAYLOR,1979; RIDGELY; TUDOR, 1994). As discussed by Snow (1982), P. carnifex and P. nigricollis would be considered the same polytypic biological species if it were not for the fact that they occur sympatrically in the lower Tapajós and Xingu rivers; however, this author warns that this relatively restricted distribution overlap needs to be better investigated in order to provide further subsidies to the taxonomic treatment of these two species. The aim of this project was to study the geographic variation of Phoenicircus species in Amazonia, from the specimen series of the Museu Paraense Emílio Goeldi, considered the largest in the world and therefore of fundamental importance for understanding the taxonomic status of P. carnifex and P. nigricollis. The geographic variation of these taxa was studied based on univariate and multivariate statistical analyses of plumage and morphometric characters, with the purpose of enabling an objective diagnosis of distinct groups and that, therefore, can be recognized as independent evolutionary units, using the phylogenetic concept of species (CRACRAFT,1983).
Systematic revision of the genus phoenicircus (birds: cotingidae) based on morphometrics and plumage characters
Keywords: Taxonomia; Phoenicircus carnifex; Phoenicircus nigricollis; CNPQ::CIENCIAS BIOLOGICAS::ZOOLOGIA::TAXONOMIA DOS GRUPOS RECENTES